2018
DOI: 10.1002/lipd.12050
|View full text |Cite
|
Sign up to set email alerts
|

Black Raspberry Seed Oil Improves Lipid Metabolism by Inhibiting Lipogenesis and Promoting Fatty‐Acid Oxidation in High‐Fat Diet‐Induced Obese Mice and db/db Mice

Abstract: The objective of this study was to evaluate the beneficial effect of α-linolenic acid-rich black raspberry seed (BRS) oil on lipid metabolism in high-fat diet (HFD)-induced obese and db/db mice. Five-week-old C57BL/6 mice were fed diets consisting of 50% calories from lard, 5% from soybean, and 5% from corn oil (HFD), or 50% calories from lard and 10% from BRS oil (HFD + BRS oil diet) for 12 weeks. Six-week-old C57BL/KsJ-db/db mice were fed diets consisting of 16% calories from soybean oil (standard diet), 8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…20(S)‐Protopanaxatriol, an aglycone steroid saponin categorized as a ginsenoside, demonstrates inhibitory activity against liver X receptor α (LXRα)‐mediated lipogenic genes such as SREBP‐1c, decreasing TAG accumulation in hepatocytes (Oh et al., 2015). Enhancement of β‐oxidation is also one of the pathways to ameliorate fatty liver (Lee et al., 2018). In β‐oxidation related gene and enzymes, the SAP inhibited the activities of CPT‐II and ACO and mRNA level of PPAR‐α (Table 5 & Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…20(S)‐Protopanaxatriol, an aglycone steroid saponin categorized as a ginsenoside, demonstrates inhibitory activity against liver X receptor α (LXRα)‐mediated lipogenic genes such as SREBP‐1c, decreasing TAG accumulation in hepatocytes (Oh et al., 2015). Enhancement of β‐oxidation is also one of the pathways to ameliorate fatty liver (Lee et al., 2018). In β‐oxidation related gene and enzymes, the SAP inhibited the activities of CPT‐II and ACO and mRNA level of PPAR‐α (Table 5 & Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 50 ] studied the effect of α-linolenic acid-rich black raspberry seed oil on the metabolism of lipids in high-fat diet–induced obese and db/db mice. It reduced the levels of non-esterified fatty acids, triacylglycerol, and total cholesterol in the liver and serum of both the obese and db/db mice.…”
Section: Health-promoting Properties Of Berry Seeds—in Vitro and In V...mentioning
confidence: 99%
“…The wild type of obese db/db mice lacking functional leptin receptors can induce fatty liver through a high-fat diet. 30 Kamimura et al 31 found that H 2 -enriched water could significantly improve the fatty liver of db/db mice, and long-term consumption could significantly control the fat and body weight, and lower plasma glucose, insulin and triglyceride levels. The function of fibroblast growth factor 21 is to stimulate fatty acids and consume glucose and promote the recognition of E-linkage.…”
Section: B Iological E Ffects Of ...mentioning
confidence: 99%